1990
DOI: 10.1111/j.1751-1097.1990.tb01968.x
|View full text |Cite
|
Sign up to set email alerts
|

ULTRAVIOLET‐RADIATION and SKIN CANCER. EFFECT OF AN OZONE LAYER DEPLETION

Abstract: The effect of changes in the ozone layer on the incidence of skin cancer was explored using data for Norway. Attempts were made to arrive at a relationship between the "environmental effective UV-dose" and the skin cancer incidence. Norway is well suited for this purpose because of the large variation in the annual UV-dose from north to south. Furthermore we have a well developed cancer registry and a homogeneous population with regard to skin type. Four different regions of the country, each with a broadness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0
6

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 9 publications
(7 reference statements)
0
34
0
6
Order By: Relevance
“…In several epidemiological studies, it has been demonstrated that increased UV radiation resulted in an increase in harmful sequelae such as skin cancer and precancerous skin lesions [1, 2, 3, 4]. In addition to UV radiation, many studies have demonstrated that skin cancers such as squamous cell carcinoma (SCC), basal cell carcinoma (BCC) and Bowen’s disease (BD) could result from ionizing radiation, chemicals, viral infection and immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…In several epidemiological studies, it has been demonstrated that increased UV radiation resulted in an increase in harmful sequelae such as skin cancer and precancerous skin lesions [1, 2, 3, 4]. In addition to UV radiation, many studies have demonstrated that skin cancers such as squamous cell carcinoma (SCC), basal cell carcinoma (BCC) and Bowen’s disease (BD) could result from ionizing radiation, chemicals, viral infection and immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ROS have been implicated to play a causal role in cancer, aging, and other degenerative diseases like arteriosclerosis, osteoarthritis, and impaired wound healing. These pathological states share unique features and are all characterized by a dysregulated localized (as is the case for cancer, invasion, and metastasis) or diffuse connective tissue breakdown due to enhanced activity of various matrix-degrading metalloproteases (3)(4)(5)(6)(7)(8)(9)(10). The family of matrix-degrading metalloproteases now comprises at least 19 members with partly distinct, partly overlapping substrate specificities for different extracellular matrix proteins of the connective tissue.…”
mentioning
confidence: 99%
“…The worldwide reported rapid rise in the incidence of these cutaneous malignancies (Glass and Hoover 1989) is almost entirely attributed to increased cutaneous exposure to solar UV radiation mostly related to present social behaviours including skin tanning and increased outdoor leisure activities (Mukhtar and Elmets 1996). Increased UV exposure due to stratospheric ozone depletion has also become a factor of concern (Henriksen et al 1990) as well as indoor sunbed exposures (Autieret al 1994(Autieret al . 1995.…”
Section: Introductionmentioning
confidence: 99%